1985
DOI: 10.3758/bf03207065
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in direction discrimination: No role for eye movements

Abstract: Practice improves observers' ability to discriminate between highly similar directions of motion. In an effort to clarify the basis for this improvement, we recorded an observer's eye movements while he made direction discriminations. We found that the observer did not need to track the moving target in order to learn the discrimination. Both at the beginning and at the end of training the observer's eye movements more closely resembled movements made while fixat-ing a stationary target, and did not at all res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A couple of studies have measured pursuit responses to obliquely moving targets. Kosnik, Fikre and Sekuler (1985) measured tracking eye movements to stimulus directions of upwards (90 deg) and three degrees to the left (93 deg) and right (87 deg) of upwards. They found that the pursuit movements were in the correct general direction although there was some error, usually within 2-8 deg.…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies have measured pursuit responses to obliquely moving targets. Kosnik, Fikre and Sekuler (1985) measured tracking eye movements to stimulus directions of upwards (90 deg) and three degrees to the left (93 deg) and right (87 deg) of upwards. They found that the pursuit movements were in the correct general direction although there was some error, usually within 2-8 deg.…”
Section: Introductionmentioning
confidence: 99%
“…Second, while fixation stability is not hampered in older adults with good acuity (i.e., normal, early AMD, and intermediate AMD), 52 , 53 it is problematic in advanced AMD impacting central vision, making it difficult to maintain image topography inside the eye. Spatial properties (e.g., density, spacing) of the cone mosaic is highly dependent on distance from the fovea, which is therefore captured in addition to specific regions of interest in large montages.…”
Section: Discussionmentioning
confidence: 99%
“…Beam Splitter Shutter the discrimination of the direction of motion is not based on the direction of tracking eye-movement responses (Holtzman, Sedgwick, & Festinger, 1978;Kosnik, Fikre, & Sekuler, 1985).…”
Section: Galvanometer Mirrormentioning
confidence: 99%